THE INFLUENCE OF SELF-EFFICACY ON STUDENTS' MATHEMATICAL REASONING ABILITIES REVIEWED FROM GENDER - Nuraeni, Sri; Herawati, Linda; Heryani, Yeni (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
To improve students' mathematical reasoning abilities, it is of course important to look at cognitive and affective aspects together, to see more broadly whether affective factors play an important role in mathematical reasoning abilities. This research aims to determine the differences in self-efficacy between male and female genders, differences in mathematical reasoning abilities between male and female genders, and the influence of self-efficacy on students' mathematical reasoning abilities in terms of gender. The research method used in this research is a correlational method with an ex post facto research design. The population of this study were all class VII students at SMP Negeri 20 Tasikmalaya. The sample in this research was obtained using non-probability sampling with a purposive sampling technique from the existing population. Classes VII-B, VII-C, VII-D, VII-E were selected as sample classes with a total of 102 students. The data collection technique is by giving a mathematical reasoning ability test and a self-efficacy questionnaire. The data analysis techniques used are descriptive statistical analysis, independent sample t-test, and two way ANOVA. Based on data processing, data analysis, and hypothesis testing, research results showed that (1) There are differences in self-efficacy between male and female genders, (2) There are no differences in students' mathematical reasoning abilities between male and female genders, (3) There is no influence of self-efficacy on students' mathematical reasoning abilities in terms of gender. These findings certainly show that affective aspects do have a role in determining students' abilities, but of course some affective aspects have a significant role, some only influence a small part.